2008
DOI: 10.1590/s1806-83242008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive cementation of zirconia posts to root dentin: evaluation of the mechanical cycling effect

Abstract: This study evaluated the effect of mechanical cycling on the bond strength of zirconia posts to root dentin. Thirty single-rooted human teeth were transversally sectioned to a length of 16 mm. The canal preparation was performed with zirconia post system drills (CosmoPost, Ivoclar) to a depth of 12 mm. For post cementation, the canals were treated with total-etch, 3-steps All-Bond 2 (Bisco), and the posts were cemented with Duolink dual resin cement (Bisco). Three groups were formed (n = 10): G1 -control, no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
5
1
1
Order By: Relevance
“…In opposition to the current study, Galhano and others, 41 employing a similar methodology, demonstrated that the push-out bond strength between a zirconia oxide post and the root dentin was significantly reduced after the dynamic fatigue test (2x10 6 cycles). This reduction is probably related to the potential of stress concentration in the root dentin when rigid zirconia oxide posts are used, 19 which may have affected adhesion between the post and dentin.…”
Section: -810-11contrasting
confidence: 99%
“…In opposition to the current study, Galhano and others, 41 employing a similar methodology, demonstrated that the push-out bond strength between a zirconia oxide post and the root dentin was significantly reduced after the dynamic fatigue test (2x10 6 cycles). This reduction is probably related to the potential of stress concentration in the root dentin when rigid zirconia oxide posts are used, 19 which may have affected adhesion between the post and dentin.…”
Section: -810-11contrasting
confidence: 99%
“…On the influence of bond strength evaluation method, Table 3 shows that the bond strength of zirconia posts to natural teeth ranged between 123 N and 436 N with tensile testing 70,71,73,81) . With push-out tests, lower values in the range of 1.4−7.7 MPa were obtained instead 63,66,72) . With regard to the reduction in bond strength values when push-out testing was used, it was caused by internal stresses at the dentin-post interface 72) .…”
Section: Resultsmentioning
confidence: 99%
“…2. Retentive strength of zirconia posts The retentive strength of zirconia posts was examined using natural teeth in 11 studies 63,65,66,[70][71][72][73]77,[80][81][82] (Table 3) and in artificial post spaces using different luting agents in five studies 68,[74][75][76]79) (Table 4). The bond strength of zirconia posts to different core materials was also examined in six studies 64,67,69,78,81,83) (Table 5), thus making it a total of 21 studies .…”
Section: Resultsmentioning
confidence: 99%
“…onde h = altura da área seccionada, R1 e R2 são obtidos através da medição dos diâmetros menor e maior da base, respectivamente, que correspondem, por sua vez, ao diâmetro interno entre as paredes radiculares do conduto (14,15). Estes valores foram obtidos utilizando paquímetro digital.…”
Section: Análise Do Padrão De Falhaunclassified